Answer:
x = 1
Step-by-step explanation:
Well the first step is to apply the distributive property:
4(3x - 1) is equal to (12x - 4). You DISTRIBUTE a '4' to what is inside the parentheses.
And btw, to make it easier, you can make 9 - x so that x is first. For example, (-x + 9). They're both the same thing, just written differently.
Your new equation is 12x - 4 = -x + 9. You want to now solve the equation.
Add the (-x) to both sides. It cancels out on the right side and you add it to 12x on the left side.
[If there's no number in front of a variable, you can always just put 1 in order to make it easier]
12x + 1x = 13x. Your new equation is 13x - 4 = 9. This should look very familiar. You simply add 4 to both sides. 9 + 4 = 13
Finally, 13x = 13. Divide 13 ÷ 13 to get 1.
x = 1
Answer:
Hotdogs are $12.00 for the dozen or $1.00 each
Bratwursts are $18.00 for the dozen or $1.50 each
Step-by-step explanation:
Answer: 13,I
Step-by-step explanation:
set the 3 number is 3/5, x,y
product of them
3 /5 xy = 7:6
xy = 7:6 x 5 /3
Xy = 13
So the two number is 13, 1
Step-by-step explanation: hope this helped, Meow!
20 cm is the answer good luck
Answer:
= 37
Step-by-step explanation:
(8+4+3) + (6+5+11)
= 15 + 22
= 37